ADVANCING RESEARCH ON MECHANISMS OF RESILIENCE (ARMOR) LONGITUDINAL COHORT STUDY OF NEW MILITARY RECRUITS: RESULTS FROM A FEASIBILITY PILOT STUDY. Issue 3 (3rd July 2021) - Polusny, Melissa A.; Marquardt, Craig A.; Hagel-Campbell, Emily; Filetti, Clarissa R.; Noël, Valentin V.; Disner, Seth G.; Schaefer, Jonathan D.; Davenport, Nicholas; Lissek, Shmuel; Noorbaloochi, Siamak; Sponheim, Scott R.; Erbes, Christopher R.
Abstract : Psychological resilience as a longitudinal process is highly relevant for understanding the functioning outcomes of military populations. Here, we review the extant literature on resilience among military service members, focusing on National Guard Soldiers. Our specific project (Advancing Research on Mechanisms of Resilience, "ARMOR") aims to develop a comprehensive model of resilience using a multilevel perspective. We report results from our prospective pilot study ( n = 103) conducted in preparation for our large-scale longitudinal cohort study of basic combat training (BCT) and its impact on military recruits' wellbeing. Results support feasibility of the larger study, evidence for a new measure of BCT stressor exposure, and demonstrate preliminary associations with BCT-related stressors and longitudinal changes in adaptive functioning. Future directions for our larger study will utilize data from survey responses, structured clinical interviews, neurobehavioral tasks, and neurobiological measures (functional and structural MRI and electroencephalography [EEG]) to examine individual differences in self-regulation as a predictor of resilience-related processes. ARMOR is well positioned to elucidate mechanisms that could be targeted for promoting wellbeing, preventing psychopathology, and facilitating long-term recovery.